2019
DOI: 10.1074/jbc.ra118.006051
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic non-histone substrate to study substrate targeting by the Gcn5 HAT and sirtuin HDACs

Abstract: Edited by John M. Denu Gcn5 and sirtuins are highly conserved histone acetyltransferase (HAT) and histone deacetylase (HDAC) enzymes that were first characterized as regulators of gene expression. Although histone tails are important substrates of these enzymes, they also target many nonhistone proteins that function in diverse biological processes. However, the mechanisms used by these enzymes to choose their nonhistone substrates are unknown. Previously, we used SILAC-based MS to identify novel nonhistone su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…GCN5 KAT activity and specificity is augmented by association with the Alteration/Deficiency in Activation (ADA) proteins [1,5], and independent ADA-GCN5 complexes have been identified in yeast and metazoans [6]. GCN5 requires association with both ADA2 and ADA3 for robust acetylation of histone and nonhistone targets [7]. GCN5 is associated with two forms of ADA2 in metazoans, termed ADA2A and ADA2B [8].…”
Section: Introductionmentioning
confidence: 99%
“…GCN5 KAT activity and specificity is augmented by association with the Alteration/Deficiency in Activation (ADA) proteins [1,5], and independent ADA-GCN5 complexes have been identified in yeast and metazoans [6]. GCN5 requires association with both ADA2 and ADA3 for robust acetylation of histone and nonhistone targets [7]. GCN5 is associated with two forms of ADA2 in metazoans, termed ADA2A and ADA2B [8].…”
Section: Introductionmentioning
confidence: 99%
“…HDACs can regulate gene expression through histone deacetylation, and some HDACs subtypes can also influence the function of non-histones and regulate a variety of cellular pathways (Lee et al, 2014). HDACs inhibitors can affect a variety of cellular effects, inhibit angiogenesis, and induce cell apoptosis (Na et al, 2010;Rossl et al, 2019). As an anti-tumor agent, HDACs inhibitors have attracted wide attention.…”
mentioning
confidence: 99%
“…Based on the sequence of ZnF3 domain from different PacC homologues in Pezizomycotina , we identified a highly conserved fragment ZnF3 (133–143) corresponding to amino acid residues 133–143 of FgPacC (Figure 7D ). Previous studies in yeast have shown that Gcn5 can target the sequences with an S-x-K-K/R-P motif ( 71 ). Notably, this putative Gcn5-binding motif (SFKRP, amino acid residues 137–141) is localized in the ZnF3 (133–143) fragment of FgPacC30.…”
Section: Resultsmentioning
confidence: 99%